Holmes Heart—A Simple Antenatal Diagnosis of a Complex Cardiac Anomaly? Fetal Echocardiographic Findings and Review. (7th February 2012) - Weichert, Jan; Axt‐Fliedner, Roland; Gembruch, Ulrich; Hartge, David R.
ABSTRACT Double inlet left ventricle as a rare cardiac malformation comprises a broad spectrum of anatomic variants making its correct antenatal diagnosis challenging. We report on echocardiographic findings of three fetuses found to have a less frequent morphologic subgroup of double inlet left ventricle, namely Holmes heart, characterized by a single (left) ventricle connected to both atrioventricular orifices and normally related arteries. We addressed the pre‐ and perinatal management as well as additional abnormalities and discussed our experiences together with what is known from current literature.